Pengembangan kemandirian anak melalui metode project-based learning di PAUD - dari, eka sari wulan (Maliki Interdisciplinary Journal, 2026)
Independence is a crucial developmental aspect for early childhood as a foundation for the next educational stage. One of the effective approaches to stimulate independence is Project-Based Learning (PjBL). This method provides opportunities for children to engage in active processes, solve problems, work collaboratively, and make decisions based on their abilities. This article aims to examine how PjBL can be implemented in early childhood education and how it influences children's independence. Based on theoretical reviews and relevant research findings, PjBL effectively increases independence through exploration activities, group responsibility, the courage to try new tasks, and the ability to select tools and materials independently. The method also enhances children’s confidence and social skills that support independence. Thus, PjBL is a highly recommended instructional strategy for consistent implementation in early childhood education settings.